Quality and reliability of IFC/BIM models for public educational facilities construction projects via clash detection - Juszczyk, Michał; Vaišnoras, Mantas; Kontrimovičius, Robertas; Hanák, Tomáš; Łukaszewska, Hanna; Ustinovichius, Leonas (Journal of Civil Engineering and Management, 2025)
This study investigates the reliability of monodiscipline IFC/BIM models in public construction projects of educational facilities through advanced clash detection and quantitative analysis. Data were collected from BIM models of two kindergartens and a school in Vilnius, Lithuania, representing different design disciplines. A mixed-methods approach was employed to analyse the number, types, and geometric characteristics of detected clashes. The research introduces innovative metrics, such as the Relative Quality Coefficient (RQC), Relative Uncertainty Coefficient (RUC), and Modified Relative Quality Coefficient (MRQC), to assess model quality and reliability quantitatively. The findings reveal a direct relationship between model complexity, clash detection precision, and the number of identified clashes, underscoring the importance of enhanced quality control measures in IFC/BIM models for public procurement. The study concludes that the implementation of these novel metrics can enhance the reliability of IFC/BIM models, thereby optimizing the design and construction process.